Penerapan Model Pembelajaran Quantum Teaching dengan Media Lingkungan Sekolah terhadap Keterampilan Proses Sains Siswa Sekolah Dasar - Gumilar, Rena Prihatna (YASIN, 2025)
Learning about science (natural science) is related to various styles because students lack skills in the science process. Therefore, efforts are needed to improve these abilities as well as moral support from school teachers through Classroom Action Research (PTK). The method used is Classroom Action Research (PTK) with stages of planning, action, observation and reflection. Data collection instruments based on observer guidance, written tests, interview sheets. Then data analysis and validation to test the accuracy of the data that appears on the research object and the data submitted by the researcher so that valid data can be produced. The results of observations of teacher performance during teaching regarding various types of styles and students also still show passive behavior. Readiness of RPP (Learning Implementation Plan), Student Worksheets (LKS) and application of the Quantum Teaching model to improve students' science process skills in class V at SDN Ciparay II, Leuwimunding District, Majalengka Regency. Teachers have not been able to combine quantum teaching learning methods into the teaching and learning process, so they only reach 70%. In Cycle II, there was an increase of 10% compared to the previous cycle and almost completely. Meanwhile, for students from initial data to cycle II, there was consistent development showing that the improvements made in each cycle contributed to increasing students' science process skills. In cycle II, all students succeeded in achieving 88%.